2013
DOI: 10.1136/jclinpath-2012-201428
|View full text |Cite
|
Sign up to set email alerts
|

Ductal carcinoma in situ associated with triple negative invasive breast cancer: evidence for a precursor–product relationship

Abstract: Our data support the notion that triple negative ductal carcinoma in situ is the precursor of the corresponding invasive counterpart, and that basal-like expression is maintained in the majority of invasive cancers associated with basal-like in situ disease. Future studies that prospectively evaluate morphological and biological characteristics of invasive cancers that develop from triple negative and basal-like ductal carcinoma in situ lesions will assist in validating these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…According to Zhou et al, the risk of recurrence for triple-negative DCIS was significantly higher amongst all the molecular subtypes after a follow-up period of 10 years [47]. Triplenegative DCIS has been found to be associated with triplenegative invasive breast cancer, and is likely to be the precursor lesion [19]. The same study found that 97.9 % of DCIS associated with triple-negative invasive breast cancer were also triple negative, suggesting that its higher occurrence amongst our cases of symptomatic DCIS may implicate aggressive behaviour of invasive recurrences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Zhou et al, the risk of recurrence for triple-negative DCIS was significantly higher amongst all the molecular subtypes after a follow-up period of 10 years [47]. Triplenegative DCIS has been found to be associated with triplenegative invasive breast cancer, and is likely to be the precursor lesion [19]. The same study found that 97.9 % of DCIS associated with triple-negative invasive breast cancer were also triple negative, suggesting that its higher occurrence amongst our cases of symptomatic DCIS may implicate aggressive behaviour of invasive recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by incubation in an oven overnight at 80°C to increase adhesion of the sections to the slides. Immunohistochemistry (IHC) was performed using antibodies to oestrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor (EGFR), and cytokeratins (CK14 and 34bE12) according to previously published protocol [19]. Details of the antibodies, dilution factors, and antigen retrieval methods are provided in Table 1.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…TMA sections (4 µm) were subjected to IHC using antibodies shown in table 1, according to published protocols 33. IHC for ER, PR and HER2 was conducted to reconfirm triple negativity; epidermal growth factor receptor (EGFR) and cytokeratins (CK14 and high molecular weight clone 34βE12) were used to detect basal-like phenotype 2.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of TRP63 is a proposed biomarker for basal cancer (Shekhar et al 2013, Thike et al 2010a) but not all investigations concur (Thike et al 2013, Buckley et al 2011). TRP63, KRT5 and smooth muscle actin (ACTA2) are expressed coordinately in normal basal mammary myoepithelial cells but are not invariably synchronously expressed in human breast cancers (Jumppanen et al 2007, Laakso et al 2005).…”
Section: Introductionmentioning
confidence: 99%